2019
DOI: 10.1177/1753495x18822581
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with polyangiitis and pregnancy: A case report and review of the literature

Abstract: The association of granulomatosis with polyangiitis and pregnancy is rare and therapeutic options are limited by the risk of teratogenicity and fetotoxicity. There is a paucity of published literature to guide clinical decision-making in these cases. We report the case of a 26-year-old woman with no medical history who presented at 21 weeks of gestation with a bilateral sudden loss of hearing and erosive rhinitis. The diagnosis of granulomatosis with polyangiitis was confirmed radiologically and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Several studies have previously shown the association between PTB and systemic vasculitides 38 or with specific systemic vasculitides subgroups 5,19,20,23–25,39,40 . Among the different subgroups, AAV presented with the most important association, as observed in the literature 2,23,41 . Our survey showed that the main factors associated with PTB were demographical factors (maternal age at delivery and comorbidities/sequelae of systemic vasculitides, including chronic renal failure) and the occurrence of vasculitides flare during pregnancy, reflecting poor disease control.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several studies have previously shown the association between PTB and systemic vasculitides 38 or with specific systemic vasculitides subgroups 5,19,20,23–25,39,40 . Among the different subgroups, AAV presented with the most important association, as observed in the literature 2,23,41 . Our survey showed that the main factors associated with PTB were demographical factors (maternal age at delivery and comorbidities/sequelae of systemic vasculitides, including chronic renal failure) and the occurrence of vasculitides flare during pregnancy, reflecting poor disease control.…”
Section: Discussionsupporting
confidence: 68%
“…5,19,20,[23][24][25]39,40 Among the different subgroups, AAV presented with the most important association, as observed in the literature. 2,23,41 Our survey showed that the main factors associated with PTB were demographical factors (maternal age at delivery and comorbidities/ sequelae of systemic vasculitides, including chronic renal failure) and the occurrence of vasculitides flare during pregnancy, reflecting poor disease control. Our results are consistent with previous findings in the general population.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, for chronic residual peripheral neuropathy in eosinophilic GPA (Churg-Strauss syndrome), the number of muscles with low manual muscle testing scores and the neuropathic pain scores also improved significantly 2 wk after IVIG administration[ 19 ], which indicated the practicality and effectiveness of IVIG treatment for eosinophilic patients with peripheral neuropathy. In addition, IVIG therapy has been safely used during pregnancy[ 20 , 21 ]. The frequency of cluster of differentiation-positive cells among the CD4+ T cells (which may promote remission in eosinophilic GPA) in the study group (IVIG therapy combined with conventional therapy) was lower than that of the control group (conventional therapy) before therapy, and was significantly increased after IVIG treatment (Table 2 )[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to possibly severe organ involvement, it is necessary to counsel women of childbearing age about the risks during pregnancy and about measures to minimize these risks [136]. In a SLR between 1970 and 2017, 87 pregnancies in 72 women with Granulomatosis with Polyangiitis were analysed [137]. A disease flare was reported in 39% of cases; PE occurred in 14% of cases, mostly women on treatment with corticosteroids.…”
Section: Pregnancy In Patients With Anca-associated Vasculitidesmentioning
confidence: 99%